Inclusion vs. Seclusion: A Review of Looking after Louis by Lesley Ely - Hirad, Hila; Vidali, Amy (Disability Studies Quarterly, 2008)
This review focuses on the messages embedded within both images and text in children's picture books. It includes a thorough analysis of Looking after Louis by Lesley Ely, detailing how its illustrations and text sometimes contradict each other, creating a complicated representation of integrated education. "Inclusion vs. Seclusion" argues that while the book attempts to offer a positive portrayal of disability in the elementary classroom, its images and text convey a negative portrayal of disability, distancing a child with a disability from his/her peers. By comparing this picture book with another closely related text, this review examines the possible effects Looking after Louis might have on young readers.